BET 1: Do patients with a clinically suspected subsegmental pulmonary embolism need anticoagulation therapy?. Issue 9 (20th August 2015) - Morgan, Chris; Choi, Hyun
Abstract : A short cut review was carried out to establish whether the incidence of recurrent venous thromboembolism and mortality is lower among patients with isolated subsegmental pulmonary embolism who are treated with anticoagulant therapy compared with those who are not treated with anticoagulant therapy. We identified six studies that were directly relevant to the question. All of these studies were observational in nature and included only a small number of patients with isolated subsegmental pulmonary embolism who were not treated with anticoagulants. Of those studies, only two included patients with confirmed isolated subsegmental pulmonary embolism that were not treated with anticoagulation. Among the 47 patients meeting those criteria, no recurrent venous thromboembolism was noted within 3 months. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. The clinical bottom line is that the limited available evidence suggests that the incident of recurrent venous thromboembolism is very low in patients with isolated subsegmental pulmonary embolism. However, this is based on limited data from small observational studies. Further evidence from larger trials is necessary before a recommendation can be made to withhold anticoagulation in this situation.